Internationalization of CR Moulds to South Africa: post entry strategy - Mkhohliso, Reed Ncwadi (2018)
The present study presents the internationalization of CR Moulds to the South African market. The aim of the study is to understand the motivations and factors that propelled CR Moulds to venture in South Africa and its plan in the market after opening a production plant in South Africa. To this end, the case study examines factors that drove CR Moulds to the South African market including dynamics encountered by the company in the market after its internationalization process to South Africa. In the main, qualitative data research was used in the case study with some primary and mostly secondary sources from government, academia and private entities. In this study, it is determined that South Africa as a market possessed general and industry specific attributes that attracted CR Moulds. Furthermore, it is also determined that institutional support including support from business associations, government, public institutions, trade and investment agencies and some monetary support is critical to small and middle sized companies such as CR Moulds especially in the immediate post entry period in foreign markets.